The Structural Manifestation of the 'Dutch Disease' : The Case of Oil Exporting Countries - Ismail, Kareem (IMF Working Papers; Working Paper ;, 2010)
This study derives structural implications of the Dutch disease in oil-exporting countries due to permanent oil price shocks from a typical model. We then test these implications in manufacturing sector data across a wide group of countries including oil-exporters covering 1977 to 2004. The results on oil-exporting countries are four folds. First, we find that permanent increases in oil price negatively impact output in manufacturing as consistent with the Dutch disease. Second, Evidence in the data shows that oil windfall shocks have a stronger impact on manufacturing sectors in countries with more open capital markets to foreign investment. Third, we find that the relative factor price of labor to capital, and capital intensity in manufacturing sectors appreciate as windfall increases. Fourth, we find that manufacturing sectors with higher capital intensity are less affected by windfall shocks than their peers, possibly due to a larger share of the effect being absorbed by more laborintensive tradable sectors. An implication of the fourth result is that having diverse manufacturing sectors in capital intensity helps cushion the volatility of oil shocks.